2014
DOI: 10.1080/1533290x.2014.945830
|View full text |Cite
|
Sign up to set email alerts
|

What Do They Have that We Don't Have? Local Libraries and Distance Students: Why Do Students Stray and Can We Get Them Back?

Abstract: A significant number of distance students report they "stray" from their home universities by using local libraries, despite the fact that distance education librarians work hard to provide customized resources and services tailored to their programs and needs. Are public libraries and special libraries able to meet the research needs of distance learners, or are these students being underserved? This article explores why distance students may choose non-academic libraries over academic libraries, and the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Public libraries serve a range of information needs within their communities, a broad range of needs to be carefully balanced in order to provide the welcoming and inclusive environment they strive to be. This is well asserted in earlier literature about public library services supporting academic study, the libraries' collection as the lens for this view (Power and Keenan, 1991;Scilken, 1993 as cited in Behr andLaDell-Thomas, 2014). However, more recently, the public library as a 'distraction-free zone' for study, as well as the provision of exam supervision, and the use of group study spaces and meeting rooms have been recognised as services that could be used by university students (Nickel and Mulvihill, 2010;Behr and LaDell-Thomas, 2014).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Public libraries serve a range of information needs within their communities, a broad range of needs to be carefully balanced in order to provide the welcoming and inclusive environment they strive to be. This is well asserted in earlier literature about public library services supporting academic study, the libraries' collection as the lens for this view (Power and Keenan, 1991;Scilken, 1993 as cited in Behr andLaDell-Thomas, 2014). However, more recently, the public library as a 'distraction-free zone' for study, as well as the provision of exam supervision, and the use of group study spaces and meeting rooms have been recognised as services that could be used by university students (Nickel and Mulvihill, 2010;Behr and LaDell-Thomas, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…This is well asserted in earlier literature about public library services supporting academic study, the libraries' collection as the lens for this view (Power and Keenan, 1991;Scilken, 1993 as cited in Behr andLaDell-Thomas, 2014). However, more recently, the public library as a 'distraction-free zone' for study, as well as the provision of exam supervision, and the use of group study spaces and meeting rooms have been recognised as services that could be used by university students (Nickel and Mulvihill, 2010;Behr and LaDell-Thomas, 2014). Findings of this study suggest that public libraries are potentially an ideal 'host' for university study, with the availability of spaces and technology, such as data projectors, printers and Internet, as well as a peer-to-peer 'connector' within their local area, and 'way finder' for students to access learning support services from the university.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…utilising their local public library alongside their university's online library. They concluded that partnerships between public libraries and universities could improve distance education students' study and learning experiences (Behr & LaDell-Thomas, 2014). Potential partnerships identified include increased promotion of academic and public libraries' services, peer networking opportunities, academic writing and research skill sessions, and exam supervision (Dority (2000) as cited in Behr & LaDell-Thomas, 2014).…”
Section: Rural Regional and Remote Low-socioeconomic Student Supportmentioning
confidence: 99%